2015
DOI: 10.1038/ijos.2015.29
|View full text |Cite|
|
Sign up to set email alerts
|

Single CD271 marker isolates mesenchymal stem cells from human dental pulp

Abstract: Mesenchymal stem cells (MSCs) are a promising tool in regenerative medicine due to their capacity to differentiate into multiple lineages. In addition to MSCs isolated from bone marrow (BMSCs), adult MSCs are isolated from craniofacial tissues including dental pulp tissues (DPs) using various stem cell surface markers. However, there has been a lack of consensus on a set of surface makers that are reproducibly effective at isolating putative multipotent dental mesenchymal stem cells (DMSCs). In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 38 publications
4
59
1
Order By: Relevance
“…This lower amount may be explained by the fact that we have excluded the CD31 + CD146 + DP cells, which represent DP endothelial cells (Nakashima et al, 2009). Conversely, the percentage of CD271 + and MSCA-1 + cells was similar to that reported in other studies (Waddington et al, 2009; Alvarez et al, 2015; Tomlinson et al, 2015, 2016; Pan et al, 2016; Yasui et al, 2016). We next investigated whether the various DP-MSC subpopulations expressed another one of these markers.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This lower amount may be explained by the fact that we have excluded the CD31 + CD146 + DP cells, which represent DP endothelial cells (Nakashima et al, 2009). Conversely, the percentage of CD271 + and MSCA-1 + cells was similar to that reported in other studies (Waddington et al, 2009; Alvarez et al, 2015; Tomlinson et al, 2015, 2016; Pan et al, 2016; Yasui et al, 2016). We next investigated whether the various DP-MSC subpopulations expressed another one of these markers.…”
Section: Discussionsupporting
confidence: 90%
“…Although no definitive MSC markers have been identified so far (Lv et al, 2014), DP-MSC populations have been characterized mainly on the basis of the expression of cell surface molecules including the bone marrow cell membrane antigen Stro-1 (Gronthos et al, 2000; Alliot-Licht et al, 2005), the melanoma cell adhesion molecule MCAM/CD146 (a marker of perivascular MSCs; Shi and Gronthos, 2003; Lv et al, 2014; Harkness et al, 2016), the low affinity nerve growth factor receptor p75NTR/CD271 (Waddington et al, 2009; Lv et al, 2014; Alvarez et al, 2015; Tomlinson et al, 2016), the mesenchymal stem cell antigen MSCA-1 (also known as TNAP/Tissue Non-Specific Alkaline Phosphatase; Sobiesiak et al, 2010; Tomlinson et al, 2015), and the neural cell adhesion molecule NCAM/CD56 (a marker of neural and muscular MSC populations; Battula et al, 2009; Sobiesiak et al, 2010; Bonnamain et al, 2013; Lv et al, 2014). We recently isolated and easily amplified in culture a population of MSCs from the DP of human developing third molars with a medicinal manufacturing approach (Ducret et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%
“…Results suggested that E19.5d EMSCs possessed stronger mineralization and odontogenesis potential. The findings were consistent with previous study: the expression levels of Dlx5 and Msx2 of p75NTR‐positive EMSCs were higher than the p75NTR‐negative EMSCs. Further, Dlx/Msx family homeodomain genes Dlx5 and msx2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in a recent study [64], the importance of CD271/NGFR in defining a subpopulation of DPSCs with enhanced odontogenic differentiation potential, as compared to other (CD51/CD140a and STRO-1/CD146) subpopulations also showing odontogenic differentiation capacity, has been emphasized. This is in accordance with studies on BMMSCs showing that CD271/NGFR defines an infrequent but very primitive subset (<1%) of the cell population showing enhanced stem cell characteristics [65].…”
Section: Localization and Immunophenotypic Characterization Of Denmentioning
confidence: 99%